Effect of Oxygen Activity on the Effectiveness of Nodulization in the Spheroidal Graphite Cast Iron Production - Nová, I.; Machuta, J. (Металлофизика и новейшие технологии, 2014)
Production of castings with spheroidal graphite iron (SGI) requires the maintenance of metallurgical and technological principles. Oxygen plays an important role in this production. The influence of oxygen on cast iron has the most significant effect on oxygen bound in oxides. Under operating conditions, it is necessary to monitor the chemical composition and temperature of the melt together with other factors, which contribute to the effect of oxygen activity and effective modifications. Influence of an applied modifier (nodulizer) of oxygen activity on the production of spheroidal graphite cast iron is established. Виробництво відливок з чавуна з кулястим графітом потребує дотримання металургійних і технологічних принципів. Кисень відіграє важливу роль в цьому виробництві. Найбільший вплив він здійснює на кисень, зв’язаний в окислах. В умовах виробництва необхідно слідкувати за хімічним складом і температурою розплаву разом з іншими факторами, які дають внесок в активність кисню та ефективні модифікації. Встановлено вплив застосованого модифікатора (ґранулятора) активності кисню на виробництво чавуна з кулястим графітом. Производство отливок из чугуна с шаровидным графитом требует соблюдения металлургических и технологических принципов. Кислород играет важную роль в этом производстве. Наибольшее влияние он оказывает на кислород, связанный в окислах. В условиях производства необходимо следить за химическим составом и температурой расплава вместе с другими факторами, которые вносят вклад в активность кислорода и эффективные модификации. Установлено влияние применяемого модификатора (гранулятора) активности кислорода на производство чугуна с шаровидным графитом.